Complementarity between the updated version of the front-of-pack nutrition label Nutri-Score and the food-processing NOVA classification - Barthélemy Sarda; Emmanuelle Kesse-Guyot; Valérie Deschamps; Pauline Ducrot; Pilar Galan; Serge Hercberg; Melanie Deschasaux-Tanguy; Bernard Srour; Leopold K Fezeu; Mathilde Touvier; Chantal Julia (Public Health Nutrition, 2024)
Abstract